Mathematical methods for construction new soliton solutions of Radhakrishnan-Kundu Lakshmanan equation - H.A. Eldidamony; Hamdy M. Ahmed; A.S. Zaghrout; Y.S. Ali; Ahmed H. Arnous (Alexandria Engineering Journal, 2022)
In this paper, the modified simple equation method and the extended simplest equation method are applied to secure optical solitons and other solutions for Radhakrishnan-Kundu Lakshmanan equation. Bright solitons, dark solitons and singular solitons are obtained. Also, periodic solutions, singular periodic solutions, rational-type solutions and hyperbolic solutions are reported. Moreover, for the physical illustration, some of the obtained solutions are represented graphically.